Assessing the Efficacy of Dengue Vaccine: A Comprehensive Literature Review - Agustina, Angelia; Alamanda, Cut Nur Cinthia (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Dengue fever remains a major global public health issue, especially in tropical nations like Indonesia, where cases of Dengue Hemorrhagic Fever (DHF) continue to increase annually. Despite extensive efforts in mosquito vector control programs, the transmission of dengue fever continues. World Health Organization (WHO) recommends vaccination as a potential option that can be used in endemic areas such as Indonesia. This literature review aims to collect and analyze the latest evidence on the efficacy and effectiveness of dengue vaccines based on findings from current relevant research. Dengvaxia, TAK-003, and TV003/TV005 are potential vaccines to provide immunity and prevent dengue infections with efficacy of Dengvaxia, DENV 3 and 4 70-80%, DENV 1 and 2 40-50%; TAK-003 seropositive 76.1%, seronegative 66.2% and TV003/TV005 seropositive 89.2% seronegative 73.6% (1-6). Additionally, TV003/TV005 can be used for travelers to endemic areas, as a single-dose administration and has been shown to provide immunity regardless of serostatus.